PENGARUH LEVERAGE, WORKING CAPITAL TURNOVER, DAN NET PROFIT MARGIN TERHADAP PROFITABILITAS PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Cut Riska Jafira; Sri Elviani; Yusrita .; Ramadona Simbolon (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2021)
The objectives in this study are whether Debt to equity ratio, Debt to assets ratio, Working capital turnover and Net profit margin simultaneously affect the Profitability projected with Return on Assets on state-owned companies listed on the Indonesia Stock Exchange. In this study, there is an influence of Debt to equity ratio, Debt to assets ratio, Working capital turnover and Net profit margin on Profitability which is projected with Return on Assets on state-owned companies listed on the Indonesia Stock Exchange.The population in this study is state-owned companies listed on the Indonesia Stock Exchange in 2017-2019.  The selection of samples in this research was conducted using purposive sampling method, which became a sample of 16 companies. The data type in this study is secondary data. The analysis method used is descriptive statistics. The results concluded that the impartiality of theDebt to assets ratio andNet profit margins had an impact on theprofitability of theDebt to equity ratio and working capital turnover did not affect the Simultaneous Productability (Test F) that the overall independent variable significantly affected profitability in state-owned companies listed on the Indonesia Stock Exchange.